"Estilo motoboy": um estudo da caracterização do profissional motofretista por meio da linguagem - Silva, Daiana Rodrigues da (2010)
This present work has as a purposal to analyze the language of the motoboys of São Paulo and the creation of a personalized slang that reflects a class of workers‟ world view that is connected to a stereotype of violence and irresponsible. We also intend, by a Conversation Analysis theory, verify how the language that individualize the group structures, when integrated with other motoboys. Then, we will have as corpus interviews and legends published photos in the site Canal Motoboy, in which 12 motoboys, armed of last generation cell phones, register the main problems of a great city as São Paulo. The study, therefore, will follow in two ways: to verify the identification of the integrants of the social group motoboys, the creation of a bow of solidarity by means of the language and, on the other hand, how the use of these words is a way of the society to confirm the negative (stereotyped) image of the professional category